Cobertura da pandemia da Covid-19: a representação da população negra capixaba nas páginas do jornal A Tribuna - Ribeiro, Isaac de Sousa (2023)
This research investigates how the black population of Espírito Santo was represented in the pages of the newspaper A Tribuna in the coverage of Covid-19 between March 2020 and August 2020. Declared a pandemic in March 2020, the SARS-CoV-2 virus was responsible for infecting and killing hundreds of thousands of people around the world. Based on Gramsci's concept of hegemony, the work seeks to investigate how the news coverage highlights and makes invisible, as well as analyzing issues related to race and identifying the meanings present in journalistic statements. From the framing and content analysis, it was possible to identify that the journalistic content of the vehicle studied does not problematize the vulnerability of black people in relation to infections and deaths, as well as exposure to the virus, difficulty in accessing health and basic hygiene conditions.